Analysis of suicide attempts due to drug poisoning during the Covid-19 pandemic in the State of Paraíba, Brazil, between 2020 and 2022 - George Soares de Mesquita; Ana Karina Holanda Leite Maia; Rafael Gomes Firmino; Pierre Bezerra Pereira; Bruno Tavares Terto de Lima; Francisco de Assis Medeiros Maia; Weslayne Nunes de Sousa; André Luiz Araújo Caetano; Francisco Patricio de Andrade Júnior (REVISTA CEREUS, 2024)
This study aimed to analyze the profile of medication-related poisonings with suicidal intent in the state of Paraíba during the COVID-19 pandemic, covering the period from 2020 to 2022. It is an epidemiological, descriptive, and analytical study based on data collected from the National Notification of Diseases Information System (SINAN). Variables such as year, gender, age group, ethnicity, education level, and clinical outcome were analyzed. The chi-square test for independence was used, with p<0.05 considered statistically significant. A total of 2,924 cases of medication-related poisoning associated with suicide attempts were reported, with 2022 being the most prevalent year (43.91%). The profile of these poisonings was predominantly female (80%), aged 20 to 39 years (51.70%), with average schooling (18%), and of mixed race (80%). A statistically significant association was found between gender and age group (p=0.001). Most cases resolved with no sequelae (80%), with a mortality rate of 0.6%. Awareness of risk factors and promoting access to mental health services are essential to mitigate the negative impacts on public health and prevent suicide-related tragedies.